The Effectiveness of Small Group-Based Psychoeducational Therapy on Self-Esteem Among Patients with Mental Illness - Nelsya Rahma; Okta Aishwa; Maulydia Maulydia (International Journal on Health and Medical Sciences, 2025)
Low self-esteem is a common psychosocial problem among individuals with mental illness and can negatively affect recovery, treatment adherence, and quality of life. Although pharmacological treatment is essential for symptom management, it often fails to adequately address psychological and social dimensions such as self-concept and self-worth. This study aimed to examine the effectiveness of small group-based psychoeducational therapy in improving self-esteem among mentally ill patients. A quantitative quasi-experimental design with a pretest–posttest approach was employed. Participants were mentally ill patients diagnosed according to DSM or ICD criteria and recruited from a mental health service setting using purposive sampling. The intervention consisted of structured psychoeducational therapy delivered in small groups over multiple sessions, focusing on illness understanding, self-acceptance, coping skills, emotional regulation, and social support. Self-esteem was measured using the Rosenberg Self-Esteem Scale before and after the intervention. Data were analyzed using paired statistical tests to assess changes in self-esteem scores. The results indicated a statistically significant increase in self-esteem following the intervention. Beyond statistical significance, the improvement reflected meaningful clinical changes, including enhanced self-acceptance, confidence, and engagement in recovery. These findings suggest that small group-based psychoeducational therapy is an effective complementary intervention for improving self-esteem in mentally ill patients. The study supports the integration of structured psychoeducational group programs into routine mental health care to promote holistic and recovery-oriented outcomes.